Interpersonal Trust and Contract Theory Redux - Anidjar, Leon (Elsevier, 2021)
The proposition that mutual loyalty facilities cooperation required for contract performance is a truism, almost a cliché. Jurists have extensively debated the role of honesty, collaboration, and reciprocity for supporting decent contractual relations. Surprisingly, contract law scholars have not developed a detailed account of interpersonal trust yet in a one-shot contract that is outside the frame of relational transactions, or the common understanding of fiduciary relations. While theoreticians acknowledge the significance of interpersonal trust as a core component of any contract theory, they fail to develop a comprehensive understanding of such concept and how it is integrated into a descriptive approach of contract law. This Article is devoted to exploring the fundamental perceptions of moral, economic, and behavioral interpersonal trust as a basis for establishing a new framework on the role of faith in contract law and theory. I show that consolidating the studies of interpersonal trust in the fundamental assumptions of promissory, efficiency, and fairness theories may fill this void and resolve some difficulties regarding their analytical force of different contract doctrines as well as provide a better justification for various transactions between a variety of contractors’ types in different legal systems.
Keywords: Interdisciplinary studies of interpersonal trust; Interpersonal trust in short term one-shot contracts; Pluralism of contract law and theory; 56 Ciencias Jurídicas y Derecho; ODS 16 - Paz, justicia e instituciones sólidas